Matching of beam phase density distribution with ion-optic characteristics of a probe-forming system in nuclear microprobe - Ponomarov, A.A.; Miroshnichenko, V.I. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The nonuniform phase density distribution of the beam particles and its nonlinear dynamic simulation in the probe-forming system used to obtain distribution profiles of the beam current density on the target subject to the conditions of a probe formation. These conditions are determined by the change of initial distribution parameters of the phase density due to the variation of position and lens excitations of a doublet of electrostatic quadrupoles. This approach allows us to find probe-forming modes when parameters of initial distribution of the beam phase density are matching up to ion optical characteristics of the probe-forming system of a microprobe. Such matching gives increase of the current density and decrease of the beam size on a spot. Основной задачей моделирования нелинейной динамики пучка в зондоформирующей системе с неравномерным распределением фазовой плотности частиц является получение профилей распределения плотности тока на мишени в зависимости от условий формирования зонда. Эти условия определяются изменением параметров начального распределения фазовой плотности в плоскости объектного коллиматора за счет выбора расположения и питания дублета электростатических квадрупольных линз. Такой подход позволяет найти режимы формирования зонда, при которых параметры начального распределения фазовой плотности пучка согласованы с ионно-оптическими характеристиками ЗФС микрозонда. Результатом согласования является увеличение плотности тока и уменьшение размеров пучка на мишени. Головним завданням моделювання нелінійної динаміки пучка в зондоформуючій системі з нерівномірним розподілом фазової щільності частинок є одержання профілів розподілу щільності струму на мішені у залежності від умов формування зонда. Ці умови визначаються зміною параметрів початкового розподілу фазової щільності в площині об'єктного коліматора за рахунок вибору розташування та живлення дублету електростатичних квадрупольних лінз. Такий підхід дозволяє знайти режими формування зонда, при яких параметри початкового розподілу фазової щільності пучка узгоджені з іонно-оптичними характеристиками ЗФС мікрозонда. Результатом узгодження є збільшення щільності струму і зменшення розмірів пучка на мішені.